Lymphocyte cytotoxicity in systemic sclerosis: no increase on short-term culture with established human cell lines. Issue 4 (August 1982) - Wright, J K; Hughes, P; Rowell, N R
Abstract : Lymphocyte cytotoxicity towards 4 established human epithelial and fibroblast cell lines was investigated in 18 patients with systemic sclerosis by means of both whole blood and peripheral blood mononuclear cells in short term (18 h) Cr-release assays. No difference in the levels of cytotoxicity was found in patients compared with 25 normal controls, even when allowance was made for the severity of the disease and the sex of patients and controls. It is suggested that long-term (3-6 days) culture may be necessary to demonstrate the increased lymphocyte cytotoxicity originally described in the disorder.